Political corruption and unjust regimes - Fabre, CMY (SAGE Publications, 2023)
A theory of political corruption must give a plausible descriptive account of what counts as politically corrupt conduct, and a plausible normative account of the reasons why (if any) such conduct is wrongful, and distinctively so. On Ceva and Ferretti’s sophisticated descriptive and normative account of corruption if and only if the act is carried out by a public official acting in her capacity as officeholder, and she knowingly acts to ends which are not congruent with the terms of her mandate. By their own admission, Ceva and Ferretti focus for the most part on just, or nearly just, regimes – which include democratic regimes. In this paper, I probe the strength and implications of their account for political corruption in clearly unjust regimes, in which individuals’ basic civil, political and socio-economic rights are routinely and systematically violated. I argue that their account does not straightforwardly apply to these cases, and that their cursory treatment of all-things-considered justified corruption in those regimes exposes a gap in their account of corruption in general.